Internet-delivered cognitive behavioural therapy for perfectionism: Targeting dysmorphic concern. (September 2019) - Johnson, Shevaugn; Egan, Sarah J.; Andersson, Gerhard; Carlbring, Per; Shafran, Roz; Wade, Tracey D.
Highlights: Internet-delivered cognitive-behavioural therapy for perfectionism (ICBT-P) was used. Perfectionism, selective attention, and dysmorphic concern (DC) were targeted. Body image disturbance, depression, anxiety, and stress were targeted. A dot-probe task was used to measure selective attention. ICBT-P demonstrated efficacy as a treatment for clinically significant DCs. Abstract: Perfectionism is an important transdiagnostic risk factor for several psychopathologies. As such, treatments targeting perfectionism have gained increased attention over recent years. While perfectionism is postulated to be an important underlying mechanism for dysmorphic concern, no research has explored the benefits of targeting perfectionism to reduce dysmorphic concern. The current study evaluated the use of Internet-delivered cognitive behavioural therapy for perfectionism (ICBT-P) with 31 participants (28 women) with high levels of dysmorphic concern to examine the impact on perfectionism, dysmorphic concern, body image disturbance, negative affect, and selective attention towards appearance-based stimuli. Using a case series design, observations were collected at baseline, at the end of a 4-week pre-treatment phase, after the 8-week ICBT-P, and 1-month post-treatment. Intent-to-treat analyses showed significant improvement from baseline to end-of-treatment and follow-up on most of the variables, with a large effect size decrease in dysmorphic concern, and decreased selective attention to BDD-body, BDD-positive, and BDD-negative words. The results of this study support the use of ICBT-P as an efficacious treatment worthy of further examination in populations who experience high levels of dysmorphic concern.